Implementation of process technology and e-commerce in efforts to increase capacity and marketing of “Omah Kripik” - Muhammad Agus Sahbana; Achmad Setiawan; Zainol Arifin; Aan Jelli Priana; Maulana Abdul Rahman; Agus Nurwahid; Novriyan Isroq Nurman Syah Putra; Abdur Rozakh (University of Merdeka Malang, 2025)
Seloliman Village is one of the banana producers with an average production of 10-15 tons per year. The